Relation between pulmonary clearance and particle burden: a Michaelis-Menten-like kinetic model. Issue 8 (August 1996) - Yu, R C; Rappaport, S M
Abstract : OBJECTIVES: To test the validity of a Michaelis-Menten-like kinetic model of pulmonary clearance of insoluble dusts. METHODS: Data were investigated from studies of pulmonary clearance in F344 rats exposed to antimony trioxide (Sb2O3), photocopy test toner, polyvinyl chloride powder (PVC), and diesel exhaust particles. The Michaelis-Menten-like model was used to develop a relation in which the pulmonary clearance half time was a linear function of lung burden. After combining all data, linear regression techniques were applied to investigate the underlying relations. With the estimated intercepts and slopes, the Michaelis-Menten-like kinetic parameters kmax (maximal clearance rate) and m1/2 (a characteristic lung burden at which kmax is reduced by 50%) were derived for the four dusts. RESULTS: The experimental data fit the linear regression very well (R2 = 0.989), suggesting that pulmonary clearance for the four dusts followed Michaelis-Menten-like kinetics. Values of the intercept terms were not significantly different among the four dusts (P = 0.294), indicating that the intrinsic clearance rates of F344 rats were the same among the four experiments. The intrinsic clearance half time was estimated to be 77.8 days, leading to an estimated kmax of 0.0089 day-1. However, the slopes of the linear relations were significantly different among the four dusts (P < 0.001). Values of m1/2 were ranked in the order of: Sb2O3 (0.69 mg) < photocopy test toner (0.97 mg) < diesel exhaust (2.49 mg) congruent to PVC (2.90 mg). CONCLUSION: This study suggests that the Michaelis-Menten-like kinetic model reasonably describes the kinetic behavior of pulmonary clearance in F344 rats. The parameters m1/2 can be used to differentiate the potency of a particular dust for impairing pulmonary clearance.